(untitled) (Proceedings of Southern Federal University. Philology, 2020)
The article analyzes various approaches to the study of irony in Russian and foreign linguistics. Irony is considered as a complex multifaceted phenomenon, its types and specific features are investigated. Particular attention is paid to the means of expression of irony, relating to different linguistic levels, in modern literary text in English and French. Key words: irony, types of irony, language means, literary text, context. DOI 10.18522/1995-0640-2020-3-38-45